2016
DOI: 10.1109/tlt.2015.2445761
|View full text |Cite
|
Sign up to set email alerts
|

Support for Augmented Reality Simulation Systems: The Effects of Scaffolding on Learning Outcomes and Behavior Patterns

Abstract: An AR-based simulation system that integrates background knowledge and experimental support (AR-SaBEr) was designed as a learning tool for teaching basic principles of electricity to ninth-grade students. The aim of this study was to investigate how supporting the learner focus on meaningful activities affects behavior and learning performance. The sample was 82 students, who were randomly assigned to two groups. The control group used AR-SaBEr with no support for recommending activities. The experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Regarding the interaction mode of students with the multimedia resources in augmented scale, we identified that the traditional method was the most used, through the use of markers of augmented reality (Image-based, 49 studies), a result that was expected by us, due to the fact that it is the tracking used since the appearance of augmented reality until today, also confirming the results presented by Chang, Wu and Hsu (2013) and Ibanez et al (2016). Another prominent feature in mobile augmented reality approaches found in SLR articles is Location-based (23 studies).…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the interaction mode of students with the multimedia resources in augmented scale, we identified that the traditional method was the most used, through the use of markers of augmented reality (Image-based, 49 studies), a result that was expected by us, due to the fact that it is the tracking used since the appearance of augmented reality until today, also confirming the results presented by Chang, Wu and Hsu (2013) and Ibanez et al (2016). Another prominent feature in mobile augmented reality approaches found in SLR articles is Location-based (23 studies).…”
Section: Discussionsupporting
confidence: 79%
“…Scaffolding is a strategy recommended in UDL to assist students in the learning task. Scaffolding strategies have been extensively used in AR applications in education (Chen et al, 2016;Ibanez, Di-Serio, Villaran-Molina, & Delgado-Kloos, 2016;Yin, Song, Tabata, Ogata, & Hwang, 2013) and have a positive effect on motivation (Ibanez et al, 2015). The use of scaffolding is consistent with the design principles introduced by Dunleavy (2014).…”
Section: User Interface and Interaction Layer Authentication (Aut) Umentioning
confidence: 79%
“…The study suggested that the cognitive load reduction should come from the development and scaffolding of adequate background knowledge related to models, modeling, and scientific content (Waight & Gillmeister, ). Another recent study that compared the performance and behavior of students learning basic principles of electricity using Augmented Reality Simulation Systems with and without scaffolding support also confirmed that students with scaffolding support showed greater learning achievement than those without such support (Ibanez, Di‐Serio, Villaran‐Molina, & Delgado‐Kloos, ).…”
Section: Interpretation and Discussionmentioning
confidence: 76%